2020
DOI: 10.31585/jbba-3-1-(1)2020
|View full text |Cite
|
Sign up to set email alerts
|

What is in It for Me? Identifying Drivers of Blockchain Acceptance among German Consumers

Abstract: From a consumers' perspective, Blockchain Technology (BCT) holds the potential to decrease transaction costs, improve privacy and redesign social interactions, which potentially leads to enhanced consumer power in transactional relationships. Nevertheless, only a few consumers use Blockchain-based applications consciously. By combining earlier research about BCT acceptance with different conceptualisations in the technology acceptance field (i.e. the Technology Acceptance Model and Rogers' Diffusion Theory), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…The TAM specifies that perceived usefulness is one of the most important factors since it focuses on the user's behavioral intention for the adoption of new technology. In the context of IoT and blockchain systems, perceived usefulness was found to be an important influencer of the intention to adopt these technologies in different studies [25,26,29,30]. Perceived usefulness is a significant predictor of the intention to use IoT services with blockchain.…”
Section: Attitude Related Factorsmentioning
confidence: 98%
See 1 more Smart Citation
“…The TAM specifies that perceived usefulness is one of the most important factors since it focuses on the user's behavioral intention for the adoption of new technology. In the context of IoT and blockchain systems, perceived usefulness was found to be an important influencer of the intention to adopt these technologies in different studies [25,26,29,30]. Perceived usefulness is a significant predictor of the intention to use IoT services with blockchain.…”
Section: Attitude Related Factorsmentioning
confidence: 98%
“…A number of studies have indicated that a perceived ease of use has a significant effect on the intention and behavior of IoT systems [12,25,31,32]. According to Knauer and Munn [30], they recommend focusing on ease of use to increase the perceived ease of use when applying blockchain technology to improve operations and enhance the user experience. Therefore, the role of perceived ease of use in the TAM is a significant factor enabling users to obtain advantages from Information Technology.…”
Section: Attitude Related Factorsmentioning
confidence: 99%
“…When people perceive a system as useful, they connect to the system a positive use-performance and they are reinforced for good performance by getting advantages out of it (Pfeffer, 1982;Schein, 1980;Vroom, 1964). Several scholars (Folkinshteyn et al, 2016;Jaoude et al, 2017;Knauer et al, 2019;Nuryyev et al, 2020) have found that Perceived Usefulness positively influences the intention to adopt Blockchain technology. Accordingly, we propose the following hypothesis:…”
Section: Hypothesis Development and Research Modelmentioning
confidence: 99%
“…On the basis of the theoretical analysis referred to above, the respective major study question is posed: What are the major aspects influencing the acceptance/adoption of blockchain-based supply chain technology in the Australian context? Prior studies addressed the issue from a variety of organisational perspectives, suggesting that decision-making regarding the use of blockchain-based supply chain technology depends on organisational and technological factors [6,[30][31][32]; contextual factors such as inter-organisational trust factors, and technical and external barriers [25,33]; the desire to take advantage of organisational, technological, and individual factors simultaneously [21,34]; and the perspective of global organisations [35]. However, most of these studies have typically explored the use of blockchain in a single industry.…”
Section: Introductionmentioning
confidence: 99%